An Examination of the Relationship Between Service Quality and Patients’ Satisfaction in the Hospital Industry - Krishnamoorthy, V.; Karthikeyan, P.; Prakash, N. (Indian Journal of Marketing, 2016)
This study attempted to measure the influence of various hospital service quality on patient's satisfaction. This study identified five dimensions of hospital service quality. These are: Clinical Care, Admission Procedure, Reliability, Trust, and Infrastructure. This study was conducted in Erode, Coimbatore, Salem, and Karur city in Tamil Nadu. This study employed the questionnaire method to collect data from the patients. Data collected were analyzed by using statistical tools such as factor analysis, multiple regression, correlation, and Cronbach's alpha. The study also supported that Clinical Care, Admission Procedure, Reliability, Trust, and Infrastructure affect patients’ satisfaction. Among the male patients, there was a significant impact of all dimensions of service quality on patients’ satisfaction ; whereas, among the female patients, it was Clinical Care and Trust. Furthermore, the highly perceived hospital service quality dimensions among the patients are Trust and Clinical Care. The study findings have significant implications for hospital administrators. This study can also used as a tool by the hospital administrator to identify various dimensions of hospital service quality where improvements are needed to enhance patients’ satisfaction.